Can we trust Diogenes Laertius? The Book I of the Lives of Eminent Philosophers as source for the poems and the laws of Solon - Leão, Delfim (2019)
Diogenes Laertius is one of the major sources for the laws of Solon, with no less than 14 (usually small) references: frs. 4a, 38g, 66/1e, 89/1b, 104b, 123c, 131–5, 144c, 145, and 149 LEÃO & RHODES. Similarly to the other principal sources, he also provides important information about several poems composed by Solon (frs. 2, 3, 9, 10, 11 and 20 WEST), whose preservation is in two cases owed to him alone (frs. 10 and 20). Notwithstanding, Diogenes tends to be rather underappreciated as a provider of historically accurate and valuable data. This paper intends to analyse more in detail each one of those pieces of information, in order to examine the degree of reliability of Diogenes in what pertains to the poetic and the legal work of the most famous sophos from antiquity.